Avoidance of mussel farms by dusky dolphins ( Lagenorhynchus obscurus ) in New Zealand - HC Pearson; RL Vaughn‐Hirshorn; M Srinivasan; B Würsig (New Zealand Journal of Marine and Freshwater Research, 2012)
We describe fine‐scale interactions between dusky dolphins and mussel farms in Admiralty Bay, New Zealand. We examined dusky dolphin presence in nearshore mussel farms, coordinated feeding behaviours in and near mussel farms, and long‐term changes in regional population abundance. Sampling methods included boat‐based surveys, focal follows, underwater observations, and photo‐identification. Correcting for area, dusky dolphins spent significantly less time inside mussel farms versus outside mussel farms and other nearshore areas (both P